Dampak Program Pekarangan Pangan Lestari Anggota KWT Jaya Mandiri Abadi di Kalurahan Tridadi Kapanewon Sleman Kabupaten Sleman - Anggun Tri Hapsari; Retno Setyowati; Putri Permatasari (AGRITEXTS: Journal of Agricultural Extension, 2025)
The Sustainable Food Yard Program (P2L) is designed to enhance household-level food security and income. Jaya Mandiri Abadi Women Farmer Group is one of the program’s implementers. Since its initiation in 2022, the group has achieved first place in the county-level home garden utilization competition that same year. The skills and knowledge gained in Jaya Mandiri Abadi are utilized by its members to implement P2L in their own homes. This study aims to describe the impact experienced by the members of Jaya Mandiri Abadi as P2L implementers. A qualitative research method with a descriptive approach was applied. Informants were selected purposively among active members of Jaya Mandiri Abadi, with data collected through in-depth interviews, participatory observations, and documentation. The study used Miles and Huberman’s interactive analysis model, while data validity was ensured through source and technique triangulation. The findings indicate that Jaya Mandiri Abadi members have experienced benefits in terms of food security and income improvement through the P2L program. Food security is reflected in the fulfillment of daily household food needs, easier physical and financial access to food, and the ability to consume a diverse and nutritious diet. Income improvement is achieved through selling harvested P2L products by consigning them to local stores, selling them through mobile vegetable vendors, or promoting them via WhatsApp groups within women farmer group, PKK (Family Welfare Movement), or neighborhood associations (RT).